OncoTherad® (MRB-CFI-1) Nanoimmunotherapy: A Promising Strategy to Treat Bacillus Calmette–Guérin-Unresponsive Non-Muscle-Invasive Bladder Cancer: Crosstalk among T-Cell CX3CR1, Immune Checkpoints, and the Toll-Like Receptor 4 Signaling Pathway - Alonso, João Carlos Cardoso; de Souza, Bianca Ribeiro; Reis, Ianny Brum [UNESP]; de Arruda Camargo, Gabriela Cardoso; de Oliveira, Gabriela; de Barros Frazão Salmazo, Maria Izabel; Gonçalves, Juliana Mattoso; de Castro Roston, José Ronaldo; Caria, Paulo Henrique Ferreira; da Silva Santos, André; de Freitas, Leandro Luiz Lopes; Billis, Athanase; et al. (MDPI, 2023)
This study assessed the safety and efficacy of OncoTherad® (MRB-CFI-1) nanoimmunotherapy for non-muscle invasive bladder cancer (NMIBC) patients unresponsive to Bacillus Calmette-Guérin (BCG) and explored its mechanisms of action in a bladder cancer microenvironment. A single-arm phase I/II study was conducted with 44 patients with NMIBC who were unresponsive to BCG treatment. Primary outcomes were pathological complete response (pCR) and relapse-free survival (RFS). Secondary outcomes comprised response duration and therapy safety. Patients’ mean age was 65 years; 59.1% of them were refractory, 31.8% relapsed, and 9.1% were intolerant to BCG. Moreover, the pCR rate after 24 months reached 72.7% (95% CI), whereas the mean RFS reached 21.4 months. Mean response duration in the pCR group was 14.3 months. No patient developed muscle-invasive or metastatic disease during treatment. Treatment-related adverse events occurred in 77.3% of patients, mostly grade 1–2 events. OncoTherad® activated the innate immune system through toll-like receptor 4, leading to increased interferon signaling. This activation played a crucial role in activating CX3CR1+ CD8 T cells, decreasing immune checkpoint molecules, and reversing immunosuppression in the bladder microenvironment. OncoTherad® has proved to be a safe and effective therapeutic option for patients with BCG-unresponsive NMIBC, besides showing likely advantages in tumor relapse prevention processes.
Keywords: bacillus Calmette–Guerin; bladder cancer; immunotherapy; nanotechnology; Oncotherad